TRENDS IN THE DEVELOPMENT OF RISK MANAGEMENT - P. Biolcheva (Trakia Journal of Sciences)
Awareness of the need for effective risk management is gaining ground, both among business organizations and in scientific publications in the field. The prospects for development in risk management must be tailored to the growing and transformative needs of Industry 4.0. The paper focuses on different directions, priorities of the Federation of European Riskmanagement Associations (Ferma). The main subject of research is placed on risk management through artificial intelligence. Both the risks of its introduction and the benefits of it have been identified.